Primary and oxidative DNA damage induced by titanium dioxide nanoparticles in salivary leukocytes: a non-invasive alternative in nanomaterials genotoxicity assessment - Fernández-Bertólez, Natalia (2022)
Introduction Metal oxide nanoparticles (NP) have a wide variety of applications in consumer products and biomedical practices. Recently, salivary leucocytes have been proposed as non-invasive alternative to peripheral blood leucocytes to evaluate the toxic effects of recent exposure to environmental contaminants, particularly those involving inhalatory or oral exposure routes. The present study aimed at evaluating the potential genotoxicity of titanium dioxide (TiO2) NP, frequently present in consumer products, in salivary leucocytes in vitro. Primary and oxidative DNA damage were evaluated by the standard alkaline comet assay and the hOGG1 enzyme incubation modification, respectively. Possible interferences of the NP with the methodological procedure or the OGG1 activity were addressed prior to analyses.